SMESEVS PROPERTIES OF DIESEL FUELS - Шевченко, О. Б (Science-based technologies, 2013)
Methyl ether of chicken fat properties are reviewed from the perspective to use it as a component of mixed biodiesel fuel. The influence of biodiesel fuel upon density, viscosity and fractional composition of diesel fuel is determined. The fact that mentioned characteristics of mixed diesel fuels are within allowances of the standart is proved.